0272 Decreased Risk of 2-Year Incidence of Alzheimer's Disease Among Older Adults Who Report Sleep Symptoms. (25th May 2022) - Mason, Brooke; Wills, Chloe; Tubbs, Andrew; Seixas, Azizi; Turner, Arlener; Jean-Louis, Girardin; Killgore, William; Grandner, Michael
Abstract: Introduction: Those with dementia or Alzheimer's Disease report an elevated amount of sleep difficulties compared to age-matched controls. Sleep-based interventions may be especially useful for this group, such as cognitive behavioral therapy for insomnia or pharmacological interventions. Therefore, it is important to expand the current understanding of the nature of sleep difficulties in those with Alzheimer's Disease. Methods: Data from the 2018 Health and Retirement Survey was collected from 17, 146 older adults. Poisson regression analyses were used to explore the relationship between Alzheimer's Disease as diagnosed by a doctor and sleep difficulties. Individuals who reported no Alzheimer's Disease in the previous wave (N=16, 751) were asked if they had since become diagnosed. N=101 individuals reported incident Alzheimer's Disease in the 2-year gap between assessments. Sleep difficulties were assessed by asking participants if they had difficulties initiating or maintaining sleep, waking up too early, and how rested they felt upon awakening. All 4 of these symptoms were coded as "never, " "sometimes, " or "often." Results: Unexpectedly, there was a significant decreased risk of developing Alzheimer's Disease among those who reported difficulties maintaining sleep (IRR=0.9962; 95%CI[0.9936, 0.9988]; p=0.004), and early morning awakenings (IRR=0.9961; 95%CI[0.9938, 0.9984]; p=0.001) "sometimes". When the model was adjusted for sex, race, ethnicity, age, and depression, a similar finding of decreased risk for Alzheimer's Disease for those who reported difficulties maintaining sleep (IRR=0.9953; 95%CI[0.9927, 0.9980]; p<0.001), and early morning awakenings (IRR=0.9954; 95%CI[0.9930, 0.9978]; p=0.001), "sometimes" were maintained. Conclusion: Although previous studies have shown that poor sleep may lead to increased risk of Alzheimer's and related dementias, the present study, which examined longitudinal data from a large, national sample of older adults, found that there was no association between frequent sleep disturbances and 2-year incidence of Alzheimer's Disease, and a small association between more mild symptoms and decreased risk. It is possible that the 2-year observation window was insufficient to detect effects. Also, there is a risk of measurement error in collecting self-reported data on sleep and Alzheimer's diagnoses. Support (If Any): The HRS (Health and Retirement Study) is sponsored by the National Institute on Aging (grant number NIA U01AG009740) and is conducted by the University of Michigan.